RETRACTED: Roles of Epigenetic Modifications in the Differentiation and Function of Pancreatic β-Cells - Xu, Fei; Liu, Jing; Na, Lixin; Chen, Linjun (Frontiers in Cell and Developmental Biology, 2020)
Diabetes, a metabolic disease with multiple causes characterized by high blood sugar, has become a public health problem. Hyperglycaemia is caused by deficiencies in insulin secretion, impairment of insulin function, or both. The insulin secreted by pancreatic β cells is the only hormone in the body that lowers blood glucose levels and plays vital roles in maintaining glucose homeostasis. Therefore, investigation of the molecular mechanisms of pancreatic β cell differentiation and function is necessary to elucidate the processes involved in the onset of diabetes. Although numerous studies have shown that transcriptional regulation is essential for the differentiation and function of pancreatic β cells, increasing evidence indicates that epigenetic mechanisms participate in controlling the fate and regulation of these cells. Epigenetics involves heritable alterations in gene expression caused by DNA methylation, histone modification and non-coding RNA activity that does not result in DNA nucleotide sequence alterations. Recent research has revealed that a variety of epigenetic modifications play an important role in the development of diabetes. Here, we review the mechanisms by which epigenetic regulation affects β cell differentiation and function.